ANALISIS PENGARUH STRUKTUR ASET, RISIKO BISNIS, PAJAK DAN LIKUIDITAS TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Listyorini Wahyu Widati; Siti Nafisah (Dinamika Akuntansi Keuangan dan Perbankan, 2017)
This study aimed to analyze the influence of the company's growth, profitability, asset structure, business risk, tax and liquidity to funding decisions on manufacturing companies listed in Indonesia Stock Exchange.The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2013-2015. Sample selection is done by purposive sampling method. Data were processed as many as 242 companies. Mechanical testing data is by using multiple linear regression analysis.The results of analysis show that the variable asset structure and tax significant positive effect on funding decision, the variable  liquidity (current ratio) significant negative effect on funding decision, while the variable  business risk does not affect to the funding decision on Manufacturing companies listed on the Indonesia Stock Exchange.Keywords: asset structure, business risk, tax, liquidity and funding decision